2009
DOI: 10.1108/01435120911006593
|View full text |Cite
|
Sign up to set email alerts
|

How library practitioners view knowledge management in libraries

Abstract: PurposeThe main purpose of this paper is to explore library practitioners' views of knowledge management (KM) and its incorporation into library practice.Design/methodology/approachThe study is based on the review of literature available in secondary sources, and the result of interviews of ten library practitioners worldwide. The respondents are purposively selected from the participants' lists of two international conferences held in 2008. The interviews were conducted through e‐mail using a short, structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“…KM is a strategic tool to manage the ever-changing library users needs". These developments are in line with what Roknuzzaman & Umemoto (2009) have suggested that library practitioners need to broaden their understanding, change traditional mindset, and to apply a holistic approach www.intechopen.com of KM system design and library practice focusing on both explicit and tacit knowledge. The following section further puts forward participants' understanding of the KM concept.…”
Section: Understanding the Concept Of Kmsupporting
confidence: 49%
See 4 more Smart Citations
“…KM is a strategic tool to manage the ever-changing library users needs". These developments are in line with what Roknuzzaman & Umemoto (2009) have suggested that library practitioners need to broaden their understanding, change traditional mindset, and to apply a holistic approach www.intechopen.com of KM system design and library practice focusing on both explicit and tacit knowledge. The following section further puts forward participants' understanding of the KM concept.…”
Section: Understanding the Concept Of Kmsupporting
confidence: 49%
“…The KM literature (Jain, 2007, Raja, Ahmad, Sinha, 2009, Roknuzzaman & Umemoto, 2009, Guru et al, 2009 Roknuzzaman & Umemoto (2009), generally the junior staff are reluctant to share their knowledge and ideas with their seniors, because they feel that there is no benefit of it. Traditionally librarians were not used to working with IT departments, however due to the emergence of the digital age and knowledge economy today librarians have to work hand-in hand with IT experts.…”
Section: Challenges/barriers To Knowledge Management In Academic Librmentioning
confidence: 99%
See 3 more Smart Citations